Praktik Penahanan Tersangka Dalam Kasus yang Diancam Pidana Dibawah 5 Tahun oleh UU ITE Dikaitkan Dengan Alasan Penahanan Berdasarkan KUHAP - Nasution, Firman; Sulistiani, Lies; Putri, Nella Sumika (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This research examines the practice of detaining suspects in defamation cases under the Information and Electronic Transactions (ITE) Law, particularly for articles with penalties of less than five years, and its conformity with the grounds for detention according to the Indonesian Criminal Procedure Code (KUHAP) from a Human Rights (HAM) perspective. Despite reduced penalties, detention practices persist based on KUHAP's subjective grounds. This study employs a normative juridical method supported by a socio-legal approach through case studies and interviews. The findings indicate that detention for ITE under 5 years is based on subjective grounds (fear of absconding, destroying/tampering with evidence, repeating the offense), assessed by investigators using various indicators. However, the application of these subjective grounds is often problematic, lacking factual validity, and prone to misuse, especially the ground of repeating the offense, which can stifle freedom of expression. This practice potentially violates the principle of detention as an ultima ratio and the presumption of innocence, drawing criticism from legal experts and civil society organizations due to its impact on human rights. This research recommends revisions to KUHAP and the ITE Law to clarify detention parameters, as well as strengthening oversight mechanisms and enhancing the capacity of law enforcement officials.